Distribusi Spasial dan Waktu Aktif Felidae Serta Satwa Mangsa di Suaka Margasatwa Bukit Rimbang Bukit Baling, Riau - Leonardus Adi Saktyari; Muhammad Ali Imron; Febri Anggriawan Widodo; Sandy Nurvianto (Faculty of Forestry Universitas Gadjah Mada, 2023)
The interaction between predators and prey has resulted in population dynamics and played a crucial role in maintaining species' populations within ecosystems. This research aimed to identify distribution and activity patterns to understand prey-predator interactions and the effect of environment and prey density on Felidae presence at Bukit Rimbang Bukit Baling Wildlife Reserve (BRBB WR), as an essential area for maintaining large mammal habitats in Sumatra. The camera traps were systematically placed in the Northeastern part of BRBB WR to collect presence data. The prey-predator interaction analysis used kernel density in RStudio. The effect of environment and prey density on Felidae presence was analyzed using a generalized linear model (GLM). The results indicated that Felidae and prey exhibited a dispersed distribution pattern, showing high activity at night and day, respectively. The Sumatran tiger, clouded leopard, leopard cat, and mouse deer had the highest overlap time (>0.50). However, the environmental and prey density had statistically non-significant effects on the presence of Felidae. Human activities in the area potentially disrupted wildlife community dynamics, although this aspect was beyond the scope of this research. This research suggested further investigation of the effects of human activities on wildlife communities in BRBB WR.